Pengaruh Kualitas Produk Dan Harga Terhadap Loyalitas Pelanggan Pada UMKM Lumpur Kentang 27 Cabang Pasar Oro-Oro Dowo Kota Malang - Anisa Febrianita Zein; Eko Boedhi Santoso; Yulis Nurul Aini (Indo Publishing, 2025)
UMKM Lumpur Kentang 27 is one of the businesses in the culinary sector in Malang that faces intense market competition. This study discusses the role of product quality and pricing in shaping customer loyalty at UMKM Lumpur Kentang 27. The aim of the research is to analyze the influence of these two variables on customer loyalty. The research adopted a quantitative method with an explanatory research approach. The results of the study indicate that the product quality variable has a positive and significant effect on customer loyalty. The price variable also has a positive and significant effect on customer loyalty. Simultaneously, both variables have a positive and significant effect on customer loyalty. The conclusion of this study recommends that UMKM are advised to maintain product quality and implement competitive pricing strategies to sustainably enhance customer loyalty.